2007
DOI: 10.1177/0145721707304077
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Diabetes Self-Management in the Mexican American Population

Abstract: The pilot study demonstrates that community health workers, as an integral part of the health care team, are effective agents in providing self-management support to persons with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 13 publications
1
72
0
Order By: Relevance
“…While not surprising, these results provide some evidence that increased delivery of intervention components can lead to improvement in A1C. Although individual patient data on intervention component exposure was not available, previous research has demonstrated a relationship with improvement in A1C and dosage of community health worker (CHW) contact (Thompson, Horton, & Flores, 2007).…”
Section: Researchmentioning
confidence: 75%
“…While not surprising, these results provide some evidence that increased delivery of intervention components can lead to improvement in A1C. Although individual patient data on intervention component exposure was not available, previous research has demonstrated a relationship with improvement in A1C and dosage of community health worker (CHW) contact (Thompson, Horton, & Flores, 2007).…”
Section: Researchmentioning
confidence: 75%
“…Of 16 studies reviewed, investigators noted that significant reductions in hemoglobin A1C values were reported in eight studies. A recent review of literature published in 2011 and 2012 assessing the evidence emerging from community-based participatory research approaches involving CHWs provided evidence of improved glycemic control or reduced risk of disease progression (2,3,7,19,43,60,61,111,116,127). Cancer screening.…”
Section: Evidence For Community Health Worker Effectiveness In the Unmentioning
confidence: 99%
“…Such programs, with emerging evidence for prevention of severe disease, reduction in acute hospital presentations, and minimising of development of chronic disease states, include diabetes education, obesity and eating disorder prevention, antismoking, cardiovascular risk, mental health promotion, illness prevention and early intervention strategies, provided in individual, family and group formats. [26][27][28][29][30][31] Some of these programs can, and should, be run initially as special public activities in other communal venues, for example, local town halls, church halls etc. But if participants are to return for more detailed information sessions or personal advice, which are highly desirable interim outcomes, they need to be able to access a local, attractive, welcoming, well maintained community health centre, convenient to shops, transport and parking.…”
Section: Persistent Long-term and Recurrent Conditionsmentioning
confidence: 99%